Existential crisis among university students in Bangladesh - Roy, Prodyut; Muhamad, Mohd Mokhtar; Che Amat, Muhammad Asyraf (Human Resource Management Academic Research Society, 2023)
Bio-psycho-social factors can cause various psychological problems which are existential in nature. For instances, psychological problems derived from death of a friend or family member, suicidal ideation, and relationship difficulties are considered as existential crisis. These existential crises exacerbates when a student enters university life, she/he faces different challenges such as adaptation to university life, lack of effective study skills, exam anxiety, adverse life events, relationship problem with family and peers, and couple relationship problems. Therefore, existential crises need to address for betterment of their academic performance. This paper discusses previous studies on existential crisis among university students in relation to 1) academic performance, 2) suicidal behaviour among university students, 3) existential crisis among students during the Covid-19 pandemic, and 4) existential therapy for university students. In conclusion, we propose that existential crisis should be exclusively addressed in education settings for improving academic performance of the students as well as their mental health.